Five-Year Incidence and Progression of Diabetic Retinopathy in Patients with Type II Diabetes in a Tertiary Care Center in Lebanon. (31st May 2017) - Mehanna, Carl-Joe; Abdul Fattah, Maamoun; Tamim, Hani; Nasrallah, Mona P.; Zreik, Raya; Haddad, Sandra S.; El-Annan, Jaafar; Raad, Samih; Haddad, Randa S.; Salti, Haytham I. S.
Abstract : Objective . To estimate the 5-year incidence of progression rate and regression rate and risk factors for diabetic retinopathy (DR) in a cohort of Lebanese patients with type II diabetes. Methods . We followed a cohort of 462 Lebanese patients with type II diabetes for over 5 years at the American University of Beirut Medical Center. Patients underwent yearly complete ophthalmic evaluation and fundus photographs and were assessed for the incidence, stage, and evolution of DR using modified Airlie House classification. Results . Among the 462 patients, 281 had no DR at baseline. The 5-year cumulative incidence of any DR was 10% (95% CI: 6–13), and only baseline microalbuminuria correlated with the development of DR (O R = 10.53, 95% CI: 4.39–25.23, p < 0.0001 ). Among the 181 patients with baseline DR, the worsening and regression rates of DR were 31.5% (95% CI: 25–38) and 9% (95% CI: 5–13), respectively. Microalbuminuria also approached statistical significance as a risk factor for DR worsening (O R = 1.89, 95% CI: 0.97–3.70, p = 0.06 ). Conclusion . The 5-year incidence of DR in this hospital-based cohort is relatively low. Microalbuminuria was independently associated with the incidence and progression of the disease. We recommend to screen patients with type II diabetes for microalbuminuria as prognostic for the development and worsening of DR.